2022
DOI: 10.1186/s10020-022-00502-8
|View full text |Cite
|
Sign up to set email alerts
|

FGF1 alleviates LPS-induced acute lung injury via suppression of inflammation and oxidative stress

Abstract: Background Acute lung injury (ALI) and its severe form, acute respiratory distress syndrome (ARDS), are devastating clinical disorders with high mortality, and for which more effective therapies are urgently needed. FGF1, the prototype member of the FGF family, is shown to exert protective effects against injurious stimuli in multiple disease models. Here we aimed to evaluate whether FGF1 pretreatment is protective against LPS-induced ALI and elucidate the potential underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In agreement with these results, systemic FGF1 treatment was found to significantly ameliorate LPS‐induced histopathological inflammatory cell infiltration and proinflammatory cytokine levels in B6 mice. In addition, FGF1 pretreatment significantly reduced LPS‐induced inflammation 62 . Again, FGF1 had a final anti‐inflammatory effect by influencing MF polarization.…”
Section: Viral Infection and Fgfsmentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement with these results, systemic FGF1 treatment was found to significantly ameliorate LPS‐induced histopathological inflammatory cell infiltration and proinflammatory cytokine levels in B6 mice. In addition, FGF1 pretreatment significantly reduced LPS‐induced inflammation 62 . Again, FGF1 had a final anti‐inflammatory effect by influencing MF polarization.…”
Section: Viral Infection and Fgfsmentioning
confidence: 86%
“…In addition, FGF1 pretreatment significantly reduced LPS-induced inflammation. 62 Again, FGF1 had a final anti-inflammatory effect by influencing MF polarization. It should be noticed that downregulating the inflammatory response to LPS may be a double-edged sword: for example, local application of FGF2, applied to help healing after trauma, was shown to increase the risk of bacterial infection.…”
Section: Fgfs and Human Virusesmentioning
confidence: 99%
“…(34) reported that heat‐killed Lactobacillus reuteri could repress toll‐like receptor 4 (TLR4) pathway in the hearts of diabetic rats. Inhibition of TLR4 expression activated Nrf2 signaling in human endometrial epithelial cells (35) and Sirt3 signaling in mice vascular smooth muscle cells (36) and enhanced SOD2 protein expression in mice lung tissues (37). These above data suggest that RL may enhance type I collagen level and decrease mitochondrial oxidative damage relating to MAPK/AP‐1 and Nrf2/Sirt3/SOD2 signaling, respectively, thereby alleviating skin wrinkle formation.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a highly inflammatory disease caused by bacteria, fungi, or viruses, which leads to organ dysfunction after infection [ 1 , 2 ]. Acute respiratory distress (ARDS) is a severe form of acute lung injury (ALI) [ 3 ]. The incidence of pulmonary dysfunction and ALI/ARDS was high in sepsis aggravating morbidity and mortality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%